Effects of preoperative stress, depression, social support, and self-compassion on resilience in surgical patients - Heejoung Lee; Hana Ko (PLoS ONE, 2025)
Background Limited research has been conducted on the psychological factors experienced by patients before surgery. This study examined the effects of preoperative stress, depression, social support, and self-compassion on the resilience of surgical patients. Methods Using convenience sampling, 150 patients admitted for surgery at Nasaret International and Seoul Barun Chuckdo Hospitals in I City, South Korea were included in the study. Data was collected from July 1–31, 2022. Using SPSS WIN 26.0, the data was analyzed using descriptive statistics, a t-test, ANOVA, Scheffé’s test, Pearson’s correlation coefficient, and multiple regression. Results Resilience exhibited a statistically significant negative correlation with surgical stress and depression, and a significant positive correlation with social support. Surgical stress, depression, and obstetrics and gynecological surgery had statistically significant negative effects on resilience, while education level and economic status had positive effects. Conclusion Enhancing resilience in surgical patients requires the development of tailored interventions to mitigate surgical stress and depression, which are patient-centered and account for educational and economic status, particularly in obstetric and gynecological surgery.